Solve the following limit. \lim_{x\to\infty}(\frac{3x^3-4x+2}{7x^3+5})

Carol Gates 2021-10-11 Answered
Solve the following limit.
\(\displaystyle\lim_{{{x}\to\infty}}{\left({\frac{{{3}{x}^{{3}}-{4}{x}+{2}}}{{{7}{x}^{{3}}+{5}}}}\right)}\)

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

izboknil3
Answered 2021-10-12 Author has 15890 answers
Divide numerator and denominator of the expression with the highest power of x in the denominator.
Thus we can write the limit expression as,
\(\displaystyle\lim_{{{x}\to\infty}}{\left({\frac{{{3}{x}^{{3}}-{4}{x}+{2}}}{{{7}{x}^{{3}}+{5}}}}\right)}=\lim_{{{x}\to\infty}}{\left({\frac{{{3}{\frac{{{x}^{{3}}}}{{{x}^{{3}}}}}-{4}{\frac{{{x}}}{{{x}^{{3}}}}}+{\frac{{{2}}}{{{x}}}}}}{{{7}{\frac{{{x}^{{3}}}}{{{x}^{{3}}}}}+{\frac{{{5}}}{{{x}^{{3}}}}}}}}\right)}\)
\(\displaystyle=\lim_{{{x}\to\infty}}{\left({\frac{{{3}-{\frac{{{4}}}{{{x}^{{2}}}}}+{\frac{{{2}}}{{{x}^{{3}}}}}}}{{{7}+{\frac{{{5}}}{{{x}^{{3}}}}}}}}\right)}\)
Now simplify the limit expression using limit properties and apply the limit value to the variable x.
The terms, \(\displaystyle\lim_{{{x}\to\infty}}{\frac{{{4}}}{{{x}^{{2}}}}},\lim_{{{x}\to\infty}}{\frac{{{2}}}{{{x}^{{3}}}}},\lim_{{{x}\to\infty}}{\frac{{{5}}}{{{x}^{{3}}}}}\) approaches 0 as x approaches infinity. In other words,
\(\displaystyle\lim_{{{x}\to\infty}}{\frac{{{4}}}{{{x}^{{2}}}}}={\frac{{{4}}}{{\infty}}}\)
\(\displaystyle={\frac{{{4}}}{{{\frac{{{1}}}{{{0}}}}}}}\)
\(\displaystyle={4}\times{\frac{{{0}}}{{{1}}}}\)
\(\displaystyle={0}\)
Similarly we get all the terms \(\displaystyle\lim_{{{x}\to\infty}}{\frac{{{4}}}{{{x}^{{2}}}}},\lim_{{{x}\to\infty}}{\frac{{{2}}}{{{x}^{{3}}}}},\lim_{{{x}\to\infty}}{\frac{{{5}}}{{{x}^{{3}}}}}\) equal to 0.
Therefore we get,
\(\displaystyle\lim_{{{x}\to\infty}}{\left({\frac{{{3}-{\frac{{{4}}}{{{x}^{{2}}}}}+{\frac{{{2}}}{{{x}^{{3}}}}}}}{{{7}+{\frac{{{5}}}{{{x}^{{3}}}}}}}}\right)}={\frac{{\lim_{{{x}\to\infty}}{\left({3}-{\frac{{{4}}}{{{x}^{{2}}}}}+{\frac{{{2}}}{{{x}^{{3}}}}}\right)}}}{{\lim_{{{x}\to\infty}}{\left({7}+{\frac{{{5}}}{{{x}^{{3}}}}}\right)}}}}\)
\(\displaystyle={\frac{{{3}-\lim_{{{x}\to\infty}}{\frac{{{4}}}{{{x}^{{2}}}}}+\lim_{{{x}\to\infty}}{\frac{{{2}}}{{{x}^{{3}}}}}}}{{{7}+\lim_{{{x}\to\infty}}{\frac{{{5}}}{{{x}^{{3}}}}}}}}\)
\(\displaystyle={\frac{{{3}-{0}+{0}}}{{{7}+{0}}}}={\frac{{{3}}}{{{7}}}}\)
Hence the limit of the given expression os \(\displaystyle{\frac{{{3}}}{{{7}}}}\)
Not exactly what you’re looking for?
Ask My Question
0
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...